SYSTEMATIC LITERATURE REVIEW: EXCLUSIVE BREASTFEEDING AND STUNTING – A PREVENTIVE APPROACH FOR HEALTH POLICY - Bancin, Lamtiur Junita; Siagian, Dumora Jenny Margaretha; Sitorus, Jonni; Silvia Darina; Sinaga, Anton Parlindungan (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: Stunting negatively impacts children’s growth, cognitive development, and future productivity. A frequently overlooked yet critical risk factor is the absence of exclusive breastfeeding (EBF). Many studies continue to explore and update the critical role and the urgency of EBF. Aims: This research aimed to identify and analyze the previous studies on the relationship between EBF and stunting to capture a comprehensive understanding of EBF’s role in stunting prevention and various associated factors. Methods: A Systematic Literature Review with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) protocol was employed through four steps – identification, screening, inclusion, and eligibility. A total of 865 articles were initially retrieved from electronic databases (Google Scholar and PubMed). Following the inclusion and exclusion criteria, 18 studies resulted in the final review. Results: There was a significant relationship between EBF and stunting incidents. Key contributing barriers are predominantly observed in families with low socioeconomic status and limited educational attainment. In addition, prevailing public perceptions and traditional cultural practices—such as pre-lacteal feeding and CF-were also identified as influential factors. Conclusion: The failure to practice EBF contributes to increased stunting, primarily due to the absence of optimal nutrition and immune protection provided by breast milk. The ignorance of EBF stems from customs and culture that have been applied from era to era. Addressing this issue requires multidimensional interventions, particularly focusing on educational and environmental support. Future research should adopt a multi-sectoral approach to inform evidence-based policy-making for more effective stunting prevention. Keywords: Children aged under 5 years, chronic nutrition, exclusive breastfeeding, stunting, systematic literature review.